A System for Specific, High-throughput Genotyping by Allele-specific Primer Extension on Microarrays - Pastinen, Tomi; Raitio, Mirja; Lindroos, Katarina; Tainola, Päivi; Peltonen, Leena; Syvänen, Ann-Christine (Genome Research, 2000)
This study describes a practical system that allows high-throughput genotyping of single nucleotide polymorphisms (SNPs) and detection of mutations by allele-specific extension on primer arrays. The method relies on the sequence-specific extension of two immobilized allele-specific primers that differ at their 3′-nucleotide defining the alleles, by a reverse transcriptase (RT) enzyme at optimized reaction conditions. We show the potential of this simple one-step procedure performed on spotted primer arrays of low redundancy by generating over 8000 genotypes for 40 mutations or SNPs. The genotypes formed three easily identifiable clusters and all known genotypes were assigned correctly. Higher degrees of multiplexing will be possible with this system as the power of discrimination between genotypes remained unaltered in the presence of over 100 amplicons in a single reaction. The enzyme-assisted reaction provides highly specific allele distinction, evidenced by its ability to detect minority sequence variants present in 5% of a sample at multiple sites. The assay format based on miniaturized reaction chambers at standard 384-well spacing on microscope slides carrying arrays with two primers per SNP for 80 samples results in low consumption of reagents and makes parallel analysis of a large number of samples convenient. In the assay one or two fluorescent nucleotide analogs are used as labels, and thus the genotyping results can be interpreted with presently available array scanners and software. The general accessibility, simple set-up, and the robust procedure of the array-based genotyping system described here will offer an easy way to increase the throughput of SNP typing in any molecular biology laboratory.
10.1101/gr.10.7.1031